"A Strong Leadership that Does Not Show": Ladies Auxiliaries as Women's First Entrance Points into the Fire Department. Issue 4 (2nd October 2017) - Moseley, Sarah
Abstract : Women first entered East Coast fire departments through forming ladies auxiliary groups, where women provided critical support services—offering assistance at the fire, holding fundraising events for the department, and building community relationships—while maintaining conventional gender roles. Exploring auxiliary work through the lens of collaboration reveals feminist strategies for creating ethos in a highly gendered workplace; this approach for studying the complexities of women's movement between background and foreground roles opens new avenues for considering women's navigation of rhetorical barriers in professional spaces.